1997
DOI: 10.1029/96ja03033
|View full text |Cite
|
Sign up to set email alerts
|

In situ ionospheric observations of severe weather‐related gravity waves and associated small‐scale plasma structure

Abstract: Abstract. On July 27, 1988, two sounding rockets were launched over a small thunderstorm cell which constituted the remnants of a large frontal event which had lasted for several hours over the eastern seaboard. One of the rockets was instrumented for detection of the electromagnetic impulse from lightning strikes and its subsequent interaction with the ionospheric plasma [Kelley et al., 1990]. The second had on board an absolute electron density probe, the results from which we report here. We present evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…These meteorological events are mostly distributed in the low-to mid-latitude and produce Atmospheric Gravity Waves (AGW) in the troposphere (Hung et al, 1979;Kelley, 1997;Laštovička, 2006;Xiao et al, 2007). The generated AGWs propagate upward and can disturb the ionosphere with a duration of hours (thunderstorm cells and tornadic storms) to even days (typhoon and cyclone).…”
Section: Discussionmentioning
confidence: 99%
“…These meteorological events are mostly distributed in the low-to mid-latitude and produce Atmospheric Gravity Waves (AGW) in the troposphere (Hung et al, 1979;Kelley, 1997;Laštovička, 2006;Xiao et al, 2007). The generated AGWs propagate upward and can disturb the ionosphere with a duration of hours (thunderstorm cells and tornadic storms) to even days (typhoon and cyclone).…”
Section: Discussionmentioning
confidence: 99%
“…However, such ideal comparisons cannot be simply performed due to the lack of the corresponding measurements. Comparisons can be drawn against studies of 5-min ionospheric sounding, such as those in , Bosˇka and Sˇauli (2001), Bosˇka et al (2003), Martinis and Manzano (1999), Sˇauli and Bosˇka (2001) and Sˇauli et al (2005), satellite or rocket measurements such as Bertin et al (1978) and Kelley (1997), arrays of ionosonds as reported in Somsikov (1991) and many others. We can compare the times of occurrence, differences and similarities in the vertical structure and source location.…”
Section: Agw and Solar Eclipsementioning
confidence: 97%
“…Gravity waves with the dominant period of 50 min were observed in the F region in rocket experiments by Kelley (1997) in association with a storm front with thunderstorm cells of a broad spectrum of space scales. The measured electron density profiles were very structured.…”
Section: Gravity Waves In the F Regionmentioning
confidence: 97%